2019
DOI: 10.2196/13895
|View full text |Cite
|
Sign up to set email alerts
|

Exploring User Needs and Preferences for Mobile Apps for Sleep Disturbance: Mixed Methods Study

Abstract: BackgroundMobile health (mHealth) apps demonstrate promise for improving sleep at scale. End-user engagement is a prerequisite for sustained use and effectiveness.ObjectiveWe assessed the needs and preferences of those with poor sleep and insomnia to inform the development of an engaging sleep app.MethodsWe triangulated results from qualitative (focus groups and app reviews) and quantitative (online survey) approaches. A total of 2 focus groups were conducted (N=9). An online survey tested themes identified fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 29 publications
1
32
0
1
Order By: Relevance
“…Some parameters, such as sociodemographic characteristics, basic health status, and individual preferences and habits, could be measured with a quick survey within an app [ 54 , 55 , 57 , 62 , 63 ]. Users also liked continuous monitoring features that allowed them to record their progress toward their goal on a daily basis (eg, health and behavior changes and adherence to an intervention) [ 40 , 42 , 43 , 45 , 58 , 64 - 67 ] or diary entries or notes that helped them track their progress [ 40 , 45 , 60 ]. Moreover, users also indicated a preference for sensor-based automated tracking as opposed to self-reported data, which they often forgot to input and found were not as convenient [ 47 , 52 , 59 , 63 , 68 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Some parameters, such as sociodemographic characteristics, basic health status, and individual preferences and habits, could be measured with a quick survey within an app [ 54 , 55 , 57 , 62 , 63 ]. Users also liked continuous monitoring features that allowed them to record their progress toward their goal on a daily basis (eg, health and behavior changes and adherence to an intervention) [ 40 , 42 , 43 , 45 , 58 , 64 - 67 ] or diary entries or notes that helped them track their progress [ 40 , 45 , 60 ]. Moreover, users also indicated a preference for sensor-based automated tracking as opposed to self-reported data, which they often forgot to input and found were not as convenient [ 47 , 52 , 59 , 63 , 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies indicated the importance of building an assessment on the basis of feedback on the acquired data; users quickly lost interest when they did not receive feedback that was customized [ 41 , 69 ]. The preference was for the mobile device to provide personalized information, including tailored intervention content matched to their basic characteristics [ 40 , 43 , 45 , 46 , 51 , 54 , 55 , 57 - 65 , 67 , 68 , 70 , 71 ] and feedback on continuous monitoring data, for example, their health and behavior progress over time, predicted possible causes and consequences of a health problem and advice on the behavior under investigation [ 41 - 43 , 47 , 49 , 52 , 53 , 58 , 59 , 63 , 68 ]. There was a strong interest among users for visualization of continuous monitoring data, for example, presenting data as graphs and tables [ 47 , 49 , 53 , 58 , 63 , 67 , 69 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There is little research on how user engagement happens and why users abandon a virtual hospital app. To the best of our knowledge, user reviews and basic app data are accessible and valuable [ 15 , 16 ], but have not been fully explored, especially for virtual hospital apps. Hence, we conducted a systematic search using statistical analysis and aspect-based content analysis to review apps of this theme, determine user engagement, and discuss user needs, expectations, concerns, and preferences for virtual hospital apps.…”
Section: Introductionmentioning
confidence: 99%